Sexually Transmitted Infections: Knowledge and factors affecting the treatment and P. Practices among reproductive age women - Saima Gul, Adila Anwar, Mehwish Mubarik, Uzma Shah, Kaneez Fatima, Gul Fatima, (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: The main purpose of this study was to find to assess the knowledge about STIs among community women of reproductive age (15-49 years) in Rawalpindi. Methodology: This study was conducted taking 150 women through multistage, cluster randomization from January to June 2017 at Rawalpindi. The ethical committee of Sarhad University, Peshawar approved the study. A self-structured, pre-tested questionnaire was used for data collection. Data analysis was done through SPSS® version 21. Results were generated in tables and graphs. Results: The mean ± SD age was 28.7 ± 9.5 years with a minimum of 19, maximum 49. Almost half of all women were age group 19-29 years & 82% were married. Eighty percent was the literacy while CPR was 53.7%. Knowledge about STIs was not sufficient (42%) yet most knew about mode of transmission of STIs (86.67%). Most women identified the factors which contribute to the spread of STIs; 97.33% said STIs are preventable while 92.67%. One third of all women had one or other STI but only 19 women knew about the disease they had. Conclusion and recommendations: Pakistan faces the persistent threat of STIs. Community women of reproductive age are at specific risk to a high risk of spread of STIs. Education, awareness and intervention at all levels by all stakeholders/ public and private are utmost required to stop STIs and their long standing complications.